2022
DOI: 10.1093/oncolo/oyab058
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns, Health Care Resource Utilization, and Cost in Patients with Myelofibrosis in the United States

Abstract: Background This study analyses treatment patterns, health care resource utilization (HCRU), and costs in patients with myelofibrosis (MF) and a subgroup treated with ruxolitinib (RUX). Materials and Methods Treatment patterns, all-cause and MF-related HCRU, and costs were analyzed in adults with MF with continuous enrollment in a commercial or the Medicare Advantage health plan in the pre-index period, defined as the 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Continued disease burden and high healthcare cost is, unfortunately, a familiar issue in the US. Real world data on treatment patterns and HCRU show high burden and high cost for a wide range of diseases [ 33 35 ], and while the development of new MG treatment options is therefore of benefit, they are unlikely to fully resolve the issues identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Continued disease burden and high healthcare cost is, unfortunately, a familiar issue in the US. Real world data on treatment patterns and HCRU show high burden and high cost for a wide range of diseases [ 33 35 ], and while the development of new MG treatment options is therefore of benefit, they are unlikely to fully resolve the issues identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Cytopenias are common in patients with MF, and patients with moderate or severe thrombocytopenia tend to have greater symptom burden, higher rates of anemia and transfusion dependence, and worse prognosis than MF patients with higher platelet counts 5–7 . Thrombocytopenia and anemia events are frequent in patients with MF receiving ruxolitinib and may require treatment dose reductions and discontinuation, which limit efficacy and survival 13 , 14 , 35 . Currently, ruxolitinib and fedratinib are not approved for MF patients with severe thrombocytopenia, 8 , 19 whereas pacritinib approval is limited to patients with platelets <50 × 10 9 /L in the United States 22 .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Thrombocytopenia and anemia events are frequent in patients with MF receiving ruxolitinib and may require treatment dose reductions and discontinuation, which limit efficacy and survival. 13,14,35 Currently, ruxolitinib and fedratinib are not approved for MF patients with severe thrombocytopenia, 8,19 whereas pacritinib approval is limited to patients with platelets <50 × 10 9 /L in the United States. 22 Accelerated approval of pacritinib was based on spleen response in a limited number of patients, and no confirmed symptom benefits are depicted in its label.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Canada of 1,031 MF patients in the Ontario provincial health database reported treatment cost of C$25,863 per patient per year, with hospitalisation and medication accounting for 66.5% and 18.6% of treatment costs, respectively (Bankar et al, 2020). Similarly, an analysis of US data reported MF-related medical costs of US$38,383 in the first 6 months post-MF diagnosis, of which inpatient stay and pharmacy costs contributed to 45.5% and 32.2% of total costs (Copher et al, 2022). However, it should be noted that hospitalisation costs in our study was likely to be underestimated as we did not include the cost of ICU or procedures during admission.…”
Section: Discussionmentioning
confidence: 99%